Nonlinear behavior of fiber reinforced cracked composite beams - Akbaş, Şeref Doğuşcan (Techno-Press, 2019)
This paper presents geometrically nonlinear behavior of cracked fiber reinforced composite beams by using finite element method with and the first shear beam theory. Total Lagrangian approach is used in the nonlinear kinematic relations. The crack model is considered as the rotational spring which separate into two parts of beams. In the nonlinear solution, the Newton-Raphson is used with incremental displacement. The effects of fibre orientation angles, the volume fraction, the crack depth and locations of the cracks on the geometrically nonlinear deflections of fiber reinforced composite are examined and discussed in numerical results. Also, the difference between geometrically linear and nonlinear solutions for the cracked fiber reinforced composite beams.
Akbas, Seref Doguscan/0000-0001-5327-3406
Keywords: fiber reinforced composite; geometrically nonlinear analysis; beams; crack; finite element method; total Lagrangian